Family and consumer sciences preventative and restorative education - Swafford, Melinda; Ramsey, Elizabeth (Cognella Academic Publishing, 2023)
Family and Consumer Sciences: Preventative and Restorative Education well prepares future educators to develop engaging lessons for their students using a variety of methodologies to address the ever-changing societal issues facing individuals and families. The text recognizes that family and consumer sciences education works to improve the lives of individuals, families, and communities, and is naturally preventative and restorative in nature.